1995
DOI: 10.1095/biolreprod52.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Sperm Penetration Factor in the Oviduct of the Golden Hamster1

Abstract: Previously, we found oviductal eggs to be significantly more penetrable and fertilizable in vitro than ovulated eggs collected from the ovarian bursa, while bursal eggs were comparable to mature (unovulated) follicular eggs. Incubation of follicular eggs with a soluble eluate of oviductal egg cumulus complexes (COF) increased sperm penetration: the activity was macromolecular, was destroyed at 56 degrees C, and was produced in the oviduct. We now report purification of this oviductal factor that enhances penet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…Nevertheless, successful fertilization in the physiological in vivo environment might be facilitated by oviductal glycoproteins (for review see Bavister, 1988). Indeed, Boatman and Magnoni (1994) have recently reported that the incubation of ovarian oocytes with purified hamster oviductin increases sperm penetration.…”
Section: Putative Biological Roles and Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, successful fertilization in the physiological in vivo environment might be facilitated by oviductal glycoproteins (for review see Bavister, 1988). Indeed, Boatman and Magnoni (1994) have recently reported that the incubation of ovarian oocytes with purified hamster oviductin increases sperm penetration.…”
Section: Putative Biological Roles and Fatementioning
confidence: 99%
“…However, this report did not address the precise site of association of the oviductal glycoprotein with the spermatozoa. Indirect immunofluorescence studies using a specific MAb (Boatman and Magnoni, 1994) showed that purified hamster oviductin binds in vitro to homologous sperm on the acrosomal crescent, however neither hamster nor human oviductin were found to associate with human sperm using the same techniques (Reuter et al, 1994). In vitro incubation of [35S]methionine-labeled proteins synthesized by bovine oviduct cultures with bull spermatozoa followed by the analysis of the solubilized sperm membranes using autoradiography and immunoblotting revealed that bovine oviductin associates with the sperm membranes (King and Killian, 1994).…”
Section: Putative Biological Roles and Fatementioning
confidence: 99%
“…In the future, gain-of-function experiments may help to confirm the importance of the Cterminal peptide of the rabbit oviductin in the development of early embryo. It was reported that oviductin has a function on fertilization [3], [4], [16], while our research suggested that oviductin also has a function on the release of early embryonic development block.…”
Section: Discussionmentioning
confidence: 45%
“…One thinks that the oviductins is necessary for the normal development of early embryos, the other thinks that the early embryo can develop normally in absence of oviductins, provided that the media were done more meticulously and the cultural environment is controlled more stringently. Recently there are many reports about the function of mammalian oviductins [1][2][3][4], but there is no report yet about any oviductin which has a definite function in the development of early embryo. In our previous studies, we have gained loss of function evidence to suggest that the rabbit 64 kDa oviductin has a function in overcoming the development block of early embryos in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The oviduct serves as an optimal environment for the transport of gametes, fertilization and early development of embryo (Roblero and Garavagno 1979;Fisher et al 1982;Forceledo et al 1982;Fuentealba et al 1988;Nieder and Macon 1987;Abe et al 1995;Boatman and Magnoni 1995;Lapointe et al 1995;Kim et al 1996a). Moreover, papers concerned with cultivation of zygots together with the oviductal epithelial cells, refer to the importance of the oviducts, too (Sathananthan et al 1990;Takeuchi et al 1992).…”
mentioning
confidence: 99%